Classical Methods and Digital Innovation: A Case Study of Arabic Language Learning Management - Mawadda Warahmah; Muh Thahilal Jahidul Hasyb; Roid Awadh Saeed ALgatnaini (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Arabic language education in Islamic boarding schools still relies on traditional methods such as memorization and rewriting of texts, especially in the disciplines of nahwu and shorof. However, in the digital era, there are efforts to integrate technology in learning as a form of innovation. Unfortunately, the implementation of this technology has not been evenly distributed, especially in remote areas that have limited internet access. Case studies at As'Adiyyah Dapoko Bantaeng Islamic Boarding School and MTs Al-Hudzaifiyah Kolaka examine how traditional methods and digital innovations are applied in Arabic language learning management and the challenges faced. The results of the interviews showed that the classical method still had an advantage in helping students memorize and understand the structure of the language in depth. Meanwhile, digital innovation provides benefits in improving students' istima' and speaking skills, even though it is hampered by limited infrastructure and access to technology. The combination of traditional and digital methods has the potential to enrich Arabic language learning in Islamic boarding schools. Classical methods remain relevant in building a solid foundation, while technology can improve interactivity and practical understanding. Therefore, infrastructure support and better access to technology are the key to optimizing Arabic language learning innovations in Islamic boarding schools, so that students can master the language more comprehensively.